ANALISIS KONSTRUKSI PENGAMAN TEBING TYPE SHEET PILE BETON - ardi, khoirul (Jurnal Mahasiswa Teknik, 2016)
The purpose of this study was to analyze the dimensions of the river bank protection structure Batang Lubuh using a type of concrete sheet pile. Calculating the dimensions of the river bank protection structure Batang Lubuh using basic assumptions of type W and land use pressure Coulomb theory. And discussion of the results obtained huge security dimension Lubuh Batang river bluff with concrete sheet pile type using W-300-1000 Kobe types with a length of 12 meters, a width of 99.6 cm and 30 cm tall or thick. Armature rod used is made of steel diameter 3.5 inch or 8.89 cm with a length of 15 meters. Board measuring 4 meters haunted, haunted board layout 2 meters below ground level .